AHCC® Supplementation to Support Immune Function to Clear Persistent Human Papillomavirus Infections - Smith, Judith A.; Gaikwad, Anjali A.; Mathew, Lata; Rech, Barbara; Faro, Jonathan P.; Lucci, Joseph A.; Bai, Yu; Olsen, Randall J.; Byrd, Teresa T. (Frontiers in Oncology, 2022)
Objective To determine the efficacy, safety, and durability of the use of AHCC supplementation for 6 months to support the host immune system to clear high-risk human papillomavirus (HPV) infections. The AHCC supplement is a proprietary, standardized extract of cultured lentinula edodes mycelia (AHCC®, Amino Up, Ltd., Sapporo, Japan) that has been shown to have unique immune modulatory benefits. Study Design This was a randomized, double-blind, placebo-controlled study (CTN: NCT02405533) in 50 women over 30 years of age with confirmed persistent high-risk HPV infections for greater than 2 years. Patients were randomized to placebo once daily for 12 months (N = 25) or AHCC 3-g supplementation by mouth once daily on empty stomach for 6 months followed by 6 months of placebo (N = 25). Every 3 months, patients were evaluated with HPV DNA and HPV RNA testing as well as a blood sample collected to evaluate a panel of immune markers including interferon-alpha, interferon-beta (IFN-β), interferon-gamma (IFN-γ), IgG1, T lymphocytes, and natural killer (NK) cell levels. At the completion of the 12-month study period, patients on the placebo arm were given the option to continue on the study to receive AHCC supplementation unblinded for 6 months with the same follow-up appointments and testing as the intervention arm. Results Fifty women with high-risk HPV were enrolled, and 41 completed the study. Fourteen (63.6%) of the 22 patients in the AHCC supplementation arm were HPV RNA/HPV DNA negative after 6 months, with 64.3% (9/14) achieving a durable response defined as being HPV RNA/HPV DNA negative 6 months off supplementation. On the placebo arm, two (10.5%) of 19 patients were HPV negative at 12 months. In the twelve placebo arm patients who elected to continue on the unblinded study, 50% (n = 6) were HPV RNA/HPV DNA negative after 6 months of AHCC supplementation. At the time of completion of the study, there were a total of 34 patients (22 blinded and 12 unblinded) who had received AHCC supplementation with an overall response rate of 58.8% that cleared HPV persistent infections. At the time of enrollment, the mean IFN-β level was 60.5 ± 37.6 pg/ml in women with confirmed persistent HPV infections. Suppression of IFN-β to less than 20 pg/ml correlated with an increase in T lymphocytes and IFN-γ and durable clearance of HPV infections in women who received AHCC supplementation. Conclusion Results from this phase II study demonstrated that AHCC 3 g once daily was effective to support the host immune system to eliminate persistent HPV infections and was well tolerated with no significant adverse side effects reported. The duration of AHCC supplementation required beyond the first negative result needs more evaluation to optimize success for durable outcomes. The suppression of the IFN-β level to less than 20 pg/ml correlated with clearance of HPV infections and merits further evaluation as a clinical tool for monitoring patients with HPV infections. Clinical Trial Registration clinicaltrials.gov/ct2/, identifier NCT02405533